Determination of the Psychological Burden of Gambling Harm in Iraq - Hewa Sattar Salih, Naji Yasser Saadoon, Ali Ahmed Kadhim (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To find out the association between psychosocial burden and the sociodemographic data such us (gender, age, social status, level of education, residential, occupational and economic status) and to assess the psychological burden among the gambler in the Iraq’s’ roulette casino Methodology: A cross-sectional design is carried throughout to assess the impact of the gamble upon gamblers psychosocial states in the Iraq’s’ roulette casino for the period of September 2nd 2018 to April 4th 2020. The present study is conducted in different settings that include roulette casino. A non-probability "purposive" sample of (232) participants is selected. An instrument was constructed for the intent of the study. It is content of (six) domains. The instrument included three parts: sociodemographic variables, gambling addiction and the psychosocial burden among the gambler in the Iraq’s’ roulette casino. The researcher used descriptive statistics tools such as frequency, percentage, mean of score and used in inferential statistics such as Chi-Square. Results: The findings of the study indicate that the study samples (65.9%) they have sever gambling addiction level, while (18.1%) they have moderate gambling addiction level and (15.9%) they have mild gambling addiction level. Also, the findings of the study indicate that (58.2) they have moderate social burden level, while (26.3%) they have sever social burden level and (15.5%) they have mild social burden level. Conclusions: There is a high significant relationship between the most sociodemographic data and psychological burden.